Rail Leveling Analysis of Turning Radius and Speed Train Passenger Cart - Ery Diniardi; Deni Almanda; Firmansyah Firmansyah; Thomas Djunaedi; Alvaro Costa Neto (Journal of Applied Sciences and Advanced Technology, 2021)
Needs consumer will tool transportation train fast fire on time now has sue Railway Corporation for Upgrade service and comfort for satisfaction para para consumer use tool transportation this in activity everyday. Look importance needs consumer will comfort use tool transportation train fire, then Writer interested for discuss comfort in journey train specifically problem journey train fire with elevation rail  in pass Bend moment drove. Analysis done from Railway Corporation with literature assistance regarding problem railway. Remember breadth existing problems on train fire, then Writer limit only on calculation point heavy carriage, the forces that occur, and balance carriage when turn without and existence rail elevation. From result analysis carried out elevation data is taken rail maximum by 110 mm, radius curvature, speed plan maximum 120 km/h. Generate speed data critical in bend without elevation rail, and speed critical in bend existence rail elevation.